Female Itinerant Migrants' Experiences Receiving Maternal Care in Healthcare Facilities; Application of the Three‐Delay Model - Joshua Sumankuuro; Fauzia Yussif; Maximillian Kolbe Domapielle (Reproductive, Female and Child Health)
ABSTRACT Background Itinerant migrants, particularly women and adolescent girls, are increasingly a significant category in West Africa due to climate change and political instability. This has led to a surge in cross‐border migration into Ghana, potentially impacting their access to prenatal care. However, cultural and personal factors make female itinerant migrants (FIMs) less privileged and constrained in access to maternal care in Ghana. A lot of research has been conducted into female itinerant trade and retail businesses and the business environment, yet little is known about maternal healthcare services utilisation among FIMs in Ghana, with specific focus on antenatal care (ANC). Knowledge about the complexities around maternal care uptake among FIMs is important for policy and programming. Objective We aimed to understand the factors faced by female itinerant migrants (also known as “Zabarima”) in receiving health facility antenatal care in Wa municipality, Ghana. Methods This was a qualitative exploratory study, involving 66 participants of 51 female itinerant migrants (FIMs), and 15 midwives. Of the total number of FIMs, 19 participated in both individual in‐depth interviews and two focus group discussions. Participants were purposively selected to provide relevant data for the study. Written informed consent was obtained from all participants. Interviews and focus group discussions were audio‐taped and transcribed. Transcripts were validated and coded using Mural and Dedoose qualitative analytical software/platforms. Based on Thaddeus and Maine's conceptualisation of the “three‐delay” model, a consistent framework was created and applied to the data analysis. To develop themes around the “third delay,” we used deductive coding. Both manual and computer coding were applied. We conducted both content and thematic analysis of the data. Results From the iteration of the data together with priori codes relative to the “third delay” of the three‐delay model, four broad themes emerged: “educational and ANC literacy of FIMs”, “language barrier between provider and FIMs”, “provider attitude and maltreatment of FIMs”, and “discrimination and stigma”. Conclusion The study found that FIMs experienced profound problems having access to care and maximising the benefits of maternal care in the study. The findings suggest that promoting maternal healthcare utilisation among FIMs require a multifaceted approach that addresses education gaps, language barriers, provider attitudes, professional ethics, and discrimination. We encourage stakeholders and the Ghana Health Service to enforce regulations against FIMs' abuse and recommends the introduction of interpreter services during maternal care provision, especially in border communities.